Adverse effects of topical corticosteroids in paediatric eczema: Australasian consensus statement. (6th March 2015) - Mooney, Emma; Rademaker, Marius; Dailey, Rebecca; Daniel, Ben S; Drummond, Catherine; Fischer, Gayle; Foster, Rachael; Grills, Claire; Halbert, Anne; Hill, Sarah; King, Emma; Leins, Elizabeth; et al.
Abstract: Atopic eczema is a chronic inflammatory disease affecting about 30% of Australian and New Zealand children. Severe eczema costs over AUD 6000/year per child in direct medical, hospital and treatment costs as well as time off work for caregivers and untold distress for the family unit. In addition, it has a negative impact on a child's sleep, education, development and self‐esteem. The treatment of atopic eczema is complex and multifaceted but a core component of therapy is to manage the inflammation with topical corticosteroids (TCS). Despite this, TCS are often underutilised by many parents due to corticosteroid phobia and unfounded concerns about their adverse effects. This has led to extended and unnecessary exacerbations of eczema for children. Contrary to popular perceptions, (TCS) use in paediatric eczema does not cause atrophy, hypopigmentation, hypertrichosis, osteoporosis, purpura or telangiectasia when used appropriately as per guidelines. In rare cases, prolonged and excessive use of potent TCS has contributed to striae, short‐term hypothalamic‐pituitary‐adrenal axis alteration and ophthalmological disease. TCS use can also exacerbate periorificial rosacea. TCS are very effective treatments for eczema. When they are used to treat active eczema and stopped once the active inflammation has resolved, adverse effects are minimal. TCS should be the cornerstone treatment of atopic eczema in children.